A novel fluorescent sensitive assay for detection of differential T cell mediated lysis of multiple adherent target cells. - Black, A; Jones, L; Ardern-Jones, M; Ogg, G (2006)
There are few studies that have investigated T cell mediated lysis of adherent cells. We have developed a novel, rapid and sensitive fluorescent dye-swap assay that allows efficient detection of adherent target cell lysis. The assay allows simultaneous use of multiple differentially sensitised targets and facilitates concomitant surface or intracellular effector cell phenotypic analysis.